1995
DOI: 10.3171/jns.1995.82.3.0481
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of controlled release of a cyclophosphamide derivative with polymers against rat gliomas

Abstract: Most malignant gliomas grow despite treatment by standard chemotherapeutic agents. The authors explored the use of an innovative drug, 4-hydroperoxycyclophosphamide (4HC), delivered via a controlled-release biodegradable polymer to determine whether local delivery would enhance efficacy. This drug is an alkylator-type chemotherapeutic agent derived from cyclophosphamide. Unlike the parent drug, which requires activation by hepatic microsomes, 4HC is active in vitro. Two rat glioma cell lines, 9L and F98, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…It should therefore be possible to increase this dosage several times while avoiding toxicity to the normal brain. Long-term survival was 50% in the in vivo model, which is similar to that reported in other studies by Brem and co-workers using different devices and drugs [17,29]. It is difficult to apply these animal results to the human situation where the tumour volume is about 1000 times larger.…”
Section: Discussionsupporting
confidence: 69%
“…It should therefore be possible to increase this dosage several times while avoiding toxicity to the normal brain. Long-term survival was 50% in the in vivo model, which is similar to that reported in other studies by Brem and co-workers using different devices and drugs [17,29]. It is difficult to apply these animal results to the human situation where the tumour volume is about 1000 times larger.…”
Section: Discussionsupporting
confidence: 69%
“…Theoretically, this strategy is expected to deliver a high drug concentration to the tumor center (by local drug implantation) and a constant level to the periphery (through systemic administration). Ideally, the drug implanted intralesionally should have a poor permeability through the BBB to prevent escape [26,27], with the systemically administered drug having a relatively high permeability through the BBB. As the permeability of cisplatin through the BBB is poor and the permeability of carmustine is relatively high, cisplatin implanted ic in polymer plus carmustine administered systemically theoretically makes good sense.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agents can also be delivered interstitially by local injection 51 or by direct implantation of drug-carrying biodegradable matrices into the debulked tumor cavity. 33,64 A 30-month trial in 240 patients found median survival times of 13.9 and 11.6 months for patients implanted with BCNU wafers or placebos, respectively. 64 However, Gliadel wafer (Eisai) implantation was found to cause adverse effects, including CSF leakage, intracranial hypertension, seizures, brain edema, healing abnormalities, and intracranial infection.…”
Section: Current Chemotherapy Route For Brain Tumorsmentioning
confidence: 99%